HOLDING AND MERGER VALUATION SCENARIO OF SOEâS INFRASTRUCTURE COMPANIES IN INDONESIA - Suryantara, Citra
Apart from government policies, State-Owned Enterprises (SOE) need to carry out a global strategy to be able to compete in the world of global competition, especially in order to increase shareholder value. Global strategies must be implemented in relation to the company's ability to increase internal strength in order to achieve a sustainable competitive advantage. PT. Hutama Karya is a state-owned company that is 100% fully owned by the Government of Indonesia which runs its business on Toll Roads, Buildings, EPC and Infrastructure. To compete in the global arena, PT. Hutama Karya must integrate with other companies either through holding or mergers. Those corporate action plans are simulated between PT. Hutama Karya, PT. Adhi Karya, PT. Waskita Karya and PT. Jasa Marga. This thesis explores the macro aspects of the construction industry by using PESTEL and Porter's five strengths, while the micro aspects of PT. Hutama Karya by using the VRIO framework approach. After that, the DCF valuation of each target company is carried out by discounting the projected free cash flow of all companies in the 10-year high growth phase as well as the stable phase. After that, the holding valuation is analyzed along with the merger valuation. The merger motive is traced as a synergy motive. Synergy Value focuses on the synergy aspects of operations that create cost efficiency and opportunities to generate greater revenue in the future. Overall, the industrial sector based on Porter's Five Forces states that the construction service industry has the following characteristics: High bargaining power of buyers / customers, high bargaining power of suppliers, and high competition among competitors. However, the threat of new arrivals is moderate and the threat of substitute products is quite low. Based on internal analysis that PT. Hutama Karya has a competitive advantage in the toll road sector where it has a strategic Asphalt Mixing Plant location, competitive patents (for road / bridge projects), the ability of global human resources to develop innovations, and a good reputation based on the awards received. Based on the results of the Target Company valuation using the DCF valuation technique, the valuation of PT. Adhi Karya and PT. Jasa Marga is undervalued, while PT. Waskita Karya is overvalued. Based on the results of the holding valuation using the DCF valuation technique, the holding valuation of PT. Hutama Karya and PT. Jasa Marga is the highest among others. Meanwhile, based on the results of the synergy assessment with the DCF valuation technique, the merger valuation of PT. Hutama Karya and PT. Adhi Karya has the highest score and is followed by PT. Adhi Karya and PT. Jasa Marga respectively. Based on calculations, PT.Hutama Karya's EBIT has the potential to continue to grow in the 10-year projection after merging with each of the target companies even though this EBIT growth is lower than that of PT. Hutama Karya itself. Based on the results of merger valuation, the highest value is obtained, namely the merger with PT. Adhi Karya. This is quite significant considering that PT. Hutama Karya is the best player in toll road construction. For other companies such as PT. Waskita Karya and PT. Jasa Marga, the passive minority holding can still be done by PT. Hutama Karya to realize the centralization of infrastructure activities without neglecting the principle of fair business competition. The limitation of this study is that the Beta value in each target company is calculated based on the majority of industries, although each target company has a variety of industries operated by its subsidiaries. The main focus in this study is operational synergy as one of the benefits of the merger. However, the authors suggest that financial synergy can become further research.